The Role of the Family Environment in Habitual Positive Behavior in Early Childhood - Lutfi Firdausi (CV. AGRAPANA MEDIA, 2026)
This study aims to examine effective strategies for fostering positive behavior in early childhood by placing the family as the primary microsystem in Bronfenbrenner's Ecological Theory. This study uses a literature review method by analyzing various relevant scientific sources related to the role of the family in shaping early childhood behavior, particularly in the context of interactions within the family microsystem. The results of the review show that the formation of positive behavior in children is influenced by several key factors, namely parental role modeling, structured daily routines, effective communication, positive reinforcement, clear rules, involving children in family activities, and supervision of digital media. All of these strategies form a consistent proximal process so that children are able to internalize moral, social, and emotional values through daily interactions. Role modeling becomes the main foundation for character building, while routines and rules support the development of self-control. Warm communication creates a sense of emotional security, and positive reinforcement increases a child's motivation to repeat good behavior. It can be concluded that the formation of positive behavior in early childhood is the result of ongoing interactions within the family system. The integration of various parenting strategies within the family microsystem creates an ecological environment that supports child development, not as a single process, but as an interrelated and continuous process.